Four new species of the genus Rhodesiella from Xizang Autonomous Region, China (Diptera: Chloropidae) - Cai, Xiaodong; Yang, Ding; Nartshuk, Emilia P.; Liu, Xiaoyan (Zootaxa, 2021)
The species of the genus Rhodesiella Adams, 1905 from Xizang of China are reviewed with the descriptions of the following four new species: R. arcuata sp. n., R. longiseta sp. n., R. perpendicularis sp. n. and R. uncata sp. n. A key to the species of Rhodesiella from Xizang is given. Comments and feature figures of new species are provided for identification. Neorhodesiella Cherian, 2002 is synonymized with Rhodesiella Adams, 1905.